Public Speaking Training as a Method for Disseminating Information and Persuasion for MSMEs in West Java - Asih Prihandini; Nungki Heriyati; Shiva Dermawan Putra (PT FORMOSA CENDEKIA GLOBAL, 2022)
Public speaking is the art or skill of speaking in front of the public which is done orally and has a specific purpose. The purpose of holding Public Speaking training is to train MSME actors to have maximum skill performance in marketing their products. Speaking and persuasion skills will be mastered when the speaker has self-management skills both physically and mentally. Having calm and confidence will enable speakers to present their products clearly and attractively. This presentation display will assist the speaker in describing and explaining the product. These skills are an absolute must for MSME actors to get customers for the products they sell. One indicator of the success of this training is that some of the participants can directly make presentations promoting themselves and the products being sold.